Effect of Different Depths of Planting and Manuring on the Growth and Survival of Poplars in the Ravine Lands-I - Singh, Bakhshish; Monappa, K. (Indian Forester, 1968)
Six treatments comprising of three depths of planting (D1-60 cm; D2-90 cm; D3-120cm) and two levels of manuring (Mo-control; i.e., no manuring and M1-manuring @ 5 kg F.Y.M. per pit) were tried for planting of Populus casale, 488 in the ravine lands along River Mahi at the Central Soil Conservation Research Station, Vasad (Gujarat). The lay out consisted of Randomised Block Design with 3 replications and a planting diatance of 3 m Ã— 3 m. The results of the study indicate that deep planting (D3) with or without manuring gave significantly better height and diameter growth as compared to the medium and shallow depths of planting (D2, D1,), there being no significant difference between the medium and shallow depths of planting.The depth of planting remaining same, manuring (M1,) gave significantly better height and diameter growth than the un-manured treatment (M0,) except in the case of shallow planting (D1) when no significant difference was observed between the manured and un-manured plants. Deep planting (D3,) prolonged the period of active growth and delayed the leaf fall of the plants. At the end of two growth seasons, the manured plants under deep and medium depths of planting (D3 M1, D2 M1) gave significantly better survival % than under shallow planting (D1 M1) while in the case of un-manured plants, the various depths of planting had no Significant effect on survival percentage,